Safety of a change of specifications of phytosterols/phytostanols as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Montaña Cámara; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Ángeles Jos; Alexandre Maciuk; Inge Mangelsdorf; Breige McNulty; Androniki Naska; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to provide an opinion on the safety of a change of the specifications of the authorised NF ‘phytosterols/phytostanols’ as a novel food (NF) pursuant to Regulation (EU) 2015/2283. This authorised NF concerns phytosterols extracted from plants and which may be presented as free sterols and stanols or esterified with food grade fatty acids. It has to contain less than 81% β‐sitosterol, less than 35% β‐sitostanol, less than 40% campesterol, less than 15% campestanol, less than 30% stigmasterol and less than 3% brassicasterol. Regarding the maximum limit of the specification parameter ‘other sterols/stanols’, the applicant asks for an increase from currently less than 3% to less than 7% to better reflect and cover the natural composition and proportions of sunflower‐based phytosterols/phytostanols, noting that the existing specifications have been established largely based on the NF when sourced from soy. No evidence was found from the literature for the genotoxicity, subchronic toxicity, chronic toxicity and carcinogenicity, and reproductive toxicity of four phytosterols which have been identified by the applicant in the NF when produced from sunflower oil. These four phytosterols, albeit at lower concentrations, are also found in the NF if produced from soy. The Panel also notes the history of multiple safety assessments of phytosterols performed by Member States and EFSA, in addition to the group ADI established by JECFA. The Panel also considers that an increase from less than 3 to less than 7% for the maximum specification limit for ‘other phytosterols’ is of no relevance regarding nutritional considerations. The Panel concludes that the NF is safe under the proposed change of the specifications.